PERUBAHAN FOKUS SISTEM PENYULUHAN PERTANIAN INDONESIA UNTUK MERESPONS TRANSFORMASI SISTEM PANGAN GLOBAL - Ibnu, Muhammad (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2023)
The transformation of the global food system affects small-scale farmers in developing countries, especially Indonesia. Although cropping intensity increases, farmers' income tends to decrease and is unstable due to the volatility of commodity prices in global markets. If extension systems continue to adhere to a 20th-century strategy of focusing on staple crops, farmers and extension systems will need to be able to compete effectively with the multinational corporations controlling the food chain. If this continues, national extension systems will likely follow the fate of agricultural extension systems in North America, Europe, and Oceania, which are gradually being streamlined or wholly abolished. This study aims to answer the question: What changes are needed by Indonesia's agricultural extension system to respond to the transformation of the global food system? This research method is a literature review. The research results show that Indonesia's agricultural extension system still has the opportunity to make a significant, long-lasting contribution to improving the income and livelihoods of smallholders. The extension system needs to change its focus, shift to high-value crops, form business groups, become market-based, build social capital, and move to a decentralized extension structure. This 21st-century extension focus is doable but requires strong leadership and commitment.